Investigating basal ganglia function using ultra-high field MRI - Abualait, Turki S. Sabrah (2012)
The basal ganglia (BG) are a group of highly interconnected nuclei that are located deep at the base of the cerebral cortex. They participate in multiple neural circuits or 'loops' with cognitive and motor areas of the cerebral cortex. The basal ganglia has primarily been thought to be involved in motor control and learning, but more recently a number of brain imaging studies have shown that the basal ganglia are involved also in cognitive function. The aim of this work is to investigate the role of the basal ganglia in cognitive control and motor learning by examining its involvement in GO/WAIT and GO/NO-GO tasks, and Motor Prediction task, respectively. Ultra-high field (7 Tesla) fMRI is used to provide higher BOLD contrast and thus higher achievable spatial resolution. A dual echo gradient echo EPI method is used to obtain high quality images from both cortical and sub-cortical regions. A common neural basis across different forms of response inhibition using GO/WAIT and GO/NO-GO cognitive paradigms is observed in the experiments of Chapter 4, as well as distinct brain regions involved in withholding and cancelling of motor responses. Using the GO/WAIT cognitive paradigm in Chapter 5 individuals with Tourette syndrome (TS) are compared to age and gender-matched control healthy subjects (CS), and it is shown that TS subjects are unable to recruit critical cortical and sub-cortical nodes that are typically involved in mediating behavioural inhibition. Furthermore, in Chapter 6, the role of the basal ganglia in motor learning is investigated using the Motor Prediction task. The findings show that the basal ganglia and midbrain regions (i.e., habenula) are involved in motor prediction and enhancing the reinforcement learning process.